SOVIET CINEMAS DURING THE YEARS OF "STAGNATION" - M. Kosinova (Вестник университета)
In the article the questions of distribution and right of Soviet cinema in the 1970's - early 1980-ies. The author examines the repertoire policy, the issues associated with the construction of cinemas, the state cinema, the issues of kinesiology and kinodocument. As discussed in the article the period is not accidentally entered into the history as the period of "stagnation", the author focuses on the theme of "stagnation" in Soviet cinema and tries to find its causes. In this regard, the main emphasis to work done on problems in the field of cinema, which led to the fall of kinodocument.